Geodesy. - Torge, Wolfgang (De Gruyter, 2001)
The third edition of this well-known textbook, first published in 1980, has been completely revised in order to adequately reflect the drastic changes which occured in the field of geodesy in the last twenty years. Reference systems are now well established by space techniques, which dominate positioning and gravity field determination. Terrestrial techniques still play an important role at local and regional applications, whereby remarkable progress has been made with respect to automatic data aquisition. Evaluation methods are now three-dimensional in principle, and have to take the gravity.